ANALISIS NILAI KONSELING ISLAM DALAM BUDAYA NYUWANG NGANTEN DI KARANGASEM BALI - Fatimatul Zahrah; Mohamat Hadori; Saifullah (Fakultas Dakwah Universitas Ibrahimy, 2023)
One of the cultures that is characteristic in Indonesia, especially in Bali, is a very unique culture, namely the nyuwang nganten wedding culture in Karangasem Bali. The Nyuwang Nganten culture is an activity one day before the marriage contract, the groom’s family brings the prospective bride to the groom’s residence for the smooth running of the contract process which is marked with a handover. This culture has been practiced since the time of our ancestors and still exists today. It’s just that the Nyuwang Nganten culture highlights a lot of controversy, in which many researchers allow or prohibit it because it is considered to complicate the marriage process. There fore, society needs an analysis of the values of Islamic teachings so that the nyuwang nganten culture can become an appropriate instrument of Islamic da’wah in matters of marriage. This study aims to describe the values of Islamic counseling contained in the nyuwang nganten culture. This research method uses a qualitative approach to the type of ethnographic research. The results of this study are the values of Islamic counseling contained in the Nyuwang Nganten culture, including preserving the khitbah process, respecting the woman’s family, maintaining responsibility, respecting customs, prioritizing good morals, maintaining the dignity of the bride and groom, providing policies in the process Nyuwang Nganten, broadcasting religion.